Severity of White Matter Lesions Correlate with Small Vessel Ischemic Stroke - Zahirah, Mutiara; Fatmawati, Heni; Wiryaning Putri, Komang Yunita (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: Stroke is the third leading cause of death globally. White matter lesions (WMLs) are often observed on brain imaging such as magnetic resonance imaging (MRI) in healthy elders and are considered as stroke predictors. Increased WMLs volume also affects small vessel stroke with worse disability. This study aimed to explore the correlation between WMLs severity and small vessel stroke subtype in acute ischemic stroke patients.Methods: A cross-sectional descriptive study was conducted using medical record data from June 2018 to October 2022. Simple randomized sampling was used, including stroke patients at Siloam Hospital, Jember. The Fazekas scale categorized WMLs, and magnetic resonance angiography (MRA) confirmed small vessel stroke etiology-based subtype. Two-tailed Spearman's Rank-Order Correlation Coefficient test was employed to describe the relationship between WMLs severity and small vessel stroke subtype. Results: From a total of 65 acute ischemic stroke patients, 39 patients were included, predominantly females (62%), aged less than 55 years old (44%) with a history of hypertension (54%) and diabetes mellitus (59%). Small vessel stroke subtype was found in 64% of patients. There was a positive correlation between WMLs and the small vessel stroke subtype in acute ischemic stroke patients (p=0.02), suggesting that a higher Fazekas scale correlated with the small vessel subtype.Conclusion: The higher the severity of WMLs, the greater the correlation with small vessel stroke subtype. Early detection of small vessel ischemic stroke in patients with severe WML may contribute to early diagnosis and prompt treatment of ischemic stroke.